2015
DOI: 10.1088/0004-637x/813/1/45
|View full text |Cite
|
Sign up to set email alerts
|

Radio Jet Feedback and Star Formation in Heavily Obscured, Hyperluminous Quasars at Redshifts ∼ 0.5–3. I. Alma Observations

Abstract: We present ALMA 870 µm (345 GHz) data for 49 high redshift (0.47< z <2.85), luminous (11.7 < log(L bol /L ) < 14.2) radio-powerful AGN, obtained to constrain cool dust emission from starbursts concurrent with highly obscured radiative-mode black hole (BH) accretion in massive galaxies which possess a small radio jet. The sample was selected from WISE with extremely steep (red) midinfrared (MIR) colors and with compact radio emission from NVSS/FIRST. Twenty-six sources are detected at 870 µm, and we find that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 136 publications
(198 reference statements)
6
78
0
Order By: Relevance
“…The WISE HotDOGs therefore do not seem to fit Figure 7. Redshift versus 850µm flux density for blue quasars , reddened quasars (This Work, Feruglio et al 2014;Brusa et al 2015) and WISE HotDOGs (Lonsdale et al 2015;Jones et al 2014Jones et al , 2015. In all cases downward triangles denote upper limits and the large blue open circle shows the stacked 850µm flux of the blue quasars from Priddey et al (2003).…”
Section: Comparison To Mid-infrared Luminous Agnmentioning
confidence: 83%
See 2 more Smart Citations
“…The WISE HotDOGs therefore do not seem to fit Figure 7. Redshift versus 850µm flux density for blue quasars , reddened quasars (This Work, Feruglio et al 2014;Brusa et al 2015) and WISE HotDOGs (Lonsdale et al 2015;Jones et al 2014Jones et al , 2015. In all cases downward triangles denote upper limits and the large blue open circle shows the stacked 850µm flux of the blue quasars from Priddey et al (2003).…”
Section: Comparison To Mid-infrared Luminous Agnmentioning
confidence: 83%
“…Eisenhardt et al 2012). We use as the basis for comparison, the SCUBA-2 850µm and ALMA 870µm flux densities of the spectroscopically confirmed WISE HotDOGs at 1.5 < z < 3.0 from Jones et al (2014Jones et al ( , 2015 and Lonsdale et al (2015). These studies provide a sample of 42 HotDOGs with secure spectroscopic redshifts overlapping the redshift range of both our reddened quasar sample and the Priddey et al (2003) optical quasars.…”
Section: Comparison To Mid-infrared Luminous Agnmentioning
confidence: 99%
See 1 more Smart Citation
“…Another population of luminous, dusty, WISE -selected AGNs were found by Lonsdale et al (2015), by combining WISE and National Radio Astronomy Observatory (NRAO) Very Large Array (VLA) Sky Survey (NVSS) (Condon et al 1998) and/or Faint Images of the Radio Sky at Twenty-cm (FIRST) (Becker et al 1995). They were selected in a similar method in the mid-IR, and are a similarly high luminosity, dust-obscured population and in this paper are known as WISE /radio AGNs.…”
Section: Introductionmentioning
confidence: 98%
“…WISE is able to find luminous, dusty, highredshift, active galaxies because the hot dust heated by AGN and/or starburst activity can be traced using the WISE 12 µm (W3) and 22 µm (W4) bands. Eisenhardt et al (2012), Bridge et al (2013) and Lonsdale et al (2015) have shown that WISE can find different classes of interesting, luminous, high-redshift, dust-obscured AGN. Eisenhardt et al (2012) and Wu et al (2012) observed galaxies with faint or undetectable flux densities in the 3.4 µm (W1) and 4.6 µm (W2) bands, and well detected fluxes in the W3 and/or W4 bands, with a radio blind selection, giving a "W1W2-dropout" selection yielding hot, dust obscured galaxies (Hot DOGs).…”
Section: Introductionmentioning
confidence: 99%